Kajian Kesesuaian Penggunaan Lahan Terhadap Indeks Potensi Lahan dan Rencana Tata Ruang Wilayah Di Kabupaten Bengkulu Tengah - Dheandra Ariza Wulandari; Shinta Permana Putri (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
Rapid regional development in Central Bengkulu Regency has driven changes in land use that may be misaligned with environmental carrying capacity and the directives of the Regional Spatial Planning (RTRW). This study aims to assess the existing land use in Central Bengkulu Regency based on the Land Potential Index (LPI) and its conformity with the applicable RTRW. The study employs a quantitative approach, utilizing secondary data comprising spatial data on land physical characteristics and land use. Analysis was conducted using Geographic Information Systems (GIS) through scoring and overlay methods. The results indicate that areas with medium and high LPI classes dominate Central Bengkulu Regency, covering 50.250% and 24.271% of the area, respectively. Land use is primarily composed of similar gardens (71.283%), shrub forests (12.773%), and large plantations (8.251%). Overall, land use is considered reasonably aligned with land potential. In terms of conformity with the RTRW, approximately 69.957% of land use is classified as suitable, while the remainder is partially suitable, unsuitable, or unidentified. The study’s implications provide an evaluative basis for more sustainable land-use planning and management in Central Bengkulu Regency. The research recommends controlling land conversion in low-LPI areas, strengthening land rehabilitation in areas that do not conform to the RTRW, and enhancing GIS-based land-use monitoring systems. This approach is expected to improve policy consistency in spatial planning, prevent land-use conflicts, and promote sustainable and resilient regional development in Central Bengkulu Regency.